Spectacle and the city : Chinese urbanities in art and popular culture - Kloet, Jeroen de; Scheen, Lena (Cities and cultures, 2013)
China is urbanizing at an unprecedented speed. Filmmakers, artists, musicians, and writers all try to come to terms with the changes of their city. How is the Chinese city-as-spectacle, visualised and thus imagined and reimagined, if not contested, in art and popular culture? What are the possible escape routes from a completely commodified cityscape? How to realign artistic expressions of the spectacle with everyday practices? The imaginations of the Chinese city in art and popular culture that this book explores are not taken as merely mirroring or reflecting "reality", on the contrary, they are part and parcel of the construction, destruction and deconstruction of that "reality". As such, these imaginations are enmeshed in the social, material and political realities that produce Chiense cityscapes. Spectacle and the City: Chinese Urbanities in Art and Popular Culture brings together essays be an interdisciplinary team of experts on Chinese cities, including world-renowned scholars like Ackbar Abbas and Chua Beng Huat, as well as leading cultural critics like Ou Ning. Aiming to steer away from an exclusive focus on Mainland China, the adjective Chinese has a cultural meaning and includes places like Singapore and Hong Kong.